Stock Returns and Volatility Spillover Dynamics between National Stock Exchange’s Overall Index and Small and Medium Enterprises’ Index - Thukral, Sonal; Kushwah, Silky Vigg; Bhatti, M. Ishaq (International Journal of Economics and Financial Issues, 2025)
This study conducts an in-depth analysis of the dynamic interrelationship between the National Stock Exchange's (NSE) primary index, NIFTY 50, and the stock index for small and medium enterprises (SMEs), EMERGE, in India. Utilizing the Granger causality test, the research aims to determine the directional causality between the two time series. Furthermore, the Generalized Autoregressive Conditional Heteroskedasticity (GARCH) model is employed to scrutinize the volatility spillover effects between the two indices using daily stock data from December 2019 to November 2023. The empirical results reveal statistically significant autoregressive volatility spillovers within both NIFTY 50 and EMERGE indices. Additionally, the study uncovers substantial cross-volatility spillover effects between the indices, indicating a bidirectional volatility transmission. Specifically, there is a statistically significant volatility spillover from NIFTY 50 to EMERGE, and conversely, from EMERGE to NIFTY 50. These findings bear critical implications for the diversification strategies within investment portfolios. They offer essential insights for investors, portfolio managers, and policymakers, especially in light of the Indian government's recent initiatives and the surge in foreign investments targeting the SME sector. The bidirectional volatility spillovers suggest that shocks in one market can significantly affect the other, thereby informing risk management and hedging strategies. Consequently, understanding these dynamic relationships is crucial for optimizing asset allocation and enhancing portfolio resilience against market fluctuations.